First Nations reserve expansion and land cover dynamics since Treaty Land Entitlement in the Prairie region of Saskatchewan, Canada - Yu, Xiaolei; Natcher, David C.; Morrissey, Christy A.; Arcand, Melissa M. (Frontiers in Environmental Science, 2025)
Since the 1990s, Treaty Land Entitlement (TLE) and Specific Claims settlements have significantly expanded First Nations reserves in Saskatchewan, Canada. Yet, the ecological impacts remain understudied, with limited systematic land-use data. This study employs geospatial analysis of open-source historical records, land cover data, and land capability assessments to evaluate reserve changes in southern Saskatchewan—a heavily agricultural region with dense First Nations populations. Between 1992 and 2024, reserve areas nearly doubled from 4,173.3 to 8,233.9 km2, substantially increasing Indigenous land holdings. Land cover analysis reveals that reserves retained disproportionately more forests and wetlands than surrounding areas, functioning as vital biodiversity refuges and carbon sinks in a predominantly agricultural landscape. However, soil assessments indicate most reserve lands are marginal for high-yield crop production, reflecting historical inequities in allocation, and highlight systemic disparities in land quality. While expansion supports diverse land uses and priorities, limited indicated that most agricultural capability restricts economic opportunities in farming while minimizing potential environmental degradation, to the few areas of high-quality land available. Reserves’ ecological value—particularly their role in preserving native habitats—contrasts with their constrained agricultural potential, underscoring the need for policies that address both sustainable management and alternative economic development. This study provides empirical evidence for Indigenous land rights discussions, illustrating how reserve lands simultaneously offer ecological benefits and face socioeconomic challenges and opportunities. Future research should prioritize community-led strategies to enhance sustainable development, ensuring land-use planning aligns with First Nations’ goals and self-determination efforts.